Seminar Membangun Karakter Mahasiswa yang Unggul di Era Society 5.0 dengan Model "Dirandra Acalapati Nispatti" - Limbong, Tonni; Panjaitan, Muhammad Iqbal; Rajagukguk, Denni M. (ULEAD : Jurnal E-Pengabdian, 2025)
The era of Society 5.0 requires students to possess strong, adaptive character and be ready to face rapid technological developments. This article discusses the implementation of the "Dirandra Acalapati Nispatti" model in building student character at Universitas Imelda Medan. This model focuses on the development of integrity, leadership, and skills in optimally utilizing technology. The study examines the implementation of seminars involving new students and faculty members as an effort to introduce values of character and skills relevant to the challenges of Society 5.0. The results show that this model effectively enhances students' leadership, communication, critical thinking, and innovation skills. Through an approach that integrates academic, social, and technological aspects, this seminar makes a positive contribution to shaping students' character, preparing them to compete in the workforce and adapt to societal changes. The study also highlights the crucial role of faculty in mentoring and developing students' competencies, as well as the importance of ongoing eval_uation to improve education quality in the digital age